Effectiveness of the STEM based TPACK Learning Model on Students 21 Century Skills in Indonesia - Muhammad Ichsan Abda; Ahmad Zain Sarnoto; Fahmi Abdul Halim; Sri Tuti Rahmawati; Miftachul Amri; Andri Kurniawan (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to determine the effectiveness of STEM-based TPACK learning models on students' 21st century skills in Indonesia. This research is a meta-analysis research by analysing 13 national and international journals published in 2021-2024. The inclusion criteria in this study are that the research comes from SINTA and Scopus indexed journals, the research must be experimental or quasi-experimental methods, research related to the STEM-based TPACK learning model, the dependent variable is related to 21st century thinking skills consisting of critical thinking and problem solving, creative, collaborative and communicative, the research has complete data to calculate the effect size value, and the research must be open access and sample size > 28 students. Data search through google scholar, ERIC, Taylor of francis and Mendeley. The data filtering process with the PRISMA method. Data analysis is quantitative analysis by calculating the effect size value with the help of the SPSS application. The results concluded that the STEM-based TPACK learning model had a positive effect on students' 21st century thinking skills in Indonesia with an average effect size value (ES = 1.09) in the high effect size category. The findings provide information for teachers that the implementation of STEM-based TPACK learning is effective in developing students' 21st century thinking skills